Family businesses, corporate social responsibility, and websites: The strategies of Italian wine firms in talking to stakeholders. Issue 7 (1st July 2019) - Iaia, Lea; Vrontis, Demetris; Maizza, Amedeo; Fait, Monica; Scorrano, Paola; Cavallo, Federica
Abstract : Purpose: The purpose of this paper is to identify the distinctive elements of CSR communications that characterize the communications models of family businesses in the Italian wine industry, and to compare them with nonfamily businesses. Design/methodology/approach: Using a case study approach, a sample of large and medium companies practicing corporate social responsibility was identified. The content of their websites was examined using content analysis and text mining (correspondence analysis techniques and word association analysis using the T-Lab software). Findings: The analysis indicates that the ownership structure nature makes a difference in the online CSR communications process. The cultural identity in both family and nonfamily businesses is founded on intangible factors such as tradition; however, being a family business is a fundamental driver in the online CSR communications process, no longer forming a bond among players in the wine industry, but rather linking with other wine family businesses. Research limitations/implications: One limitation of this work is the small size of the investigated sample. An added value it contributes is its focus on the Italian wine industry. The paper provides the essential elements that family and nonfamily wine businesses should consider in customizing their CSR communications with the brand's specific details. Originality/value: The authors highlighted the similarities and differences of family and nonfamily wine businesses in terms of their online CSR communications. The authors also observed how the family wine business identity, in its multidimensional construct, has common factors with what we call "familiness." This research could establish a starting point for further work within this important sector.